Auxiliary Subunits Control Function and Subcellular Distribution of AMPA Receptor Complexes in NG2 Glia of the Developing Hippocampus - Stefan Hardt; Dario Tascio; Stefan Passlick; Aline Timmermann; Ronald Jabs; Christian Steinhäuser; Gerald Seifert (Frontiers in Cellular Neuroscience, 2021)
Synaptic and axonal glutamatergic signaling to NG2 glia in white matter is critical for the cells’ differentiation and activity dependent myelination. However, in gray matter the impact of neuron-to-NG2 glia signaling is still elusive, because most of these cells keep their non-myelinating phenotype throughout live. Early in postnatal development, hippocampal NG2 glia express AMPA receptors with a significant Ca2+ permeability allowing for plasticity of the neuron-glia synapses, but whether this property changes by adulthood is not known. Moreover, it is unclear whether NG2 glia express auxiliary transmembrane AMPA receptor related proteins (TARPs), which modify AMPA receptor properties, including their Ca2+ permeability. Through combined molecular and functional analyses, here we show that hippocampal NG2 glia abundantly express TARPs γ4, γ7, and γ8 as well as cornichon (CNIH)-2. TARP γ8 undergoes profound downregulation during development. Receptors of adult NG2 glia showed an increased sensitivity to blockers of Ca2+ permeable AMPA receptors, but this increase mainly concerned receptors located close to the soma. Evoked synaptic currents of NG2 glia were also sensitive to blockers of Ca2+ permeable AMPA receptors. The presence of AMPA receptors with varying Ca2+ permeability during postnatal maturation may be important for the cells’ ability to sense and respond to local glutamatergic activity and for regulating process motility, differentiation, and proliferation.